Evaluation of total keratometry and its accuracy for intraocular lens power calculation in eyes after corneal refractive surgery. Issue 10 (October 2019) - Wang, Li; Spektor, Tatyana; de Souza, Rodrigo G.; Koch, Douglas D.
Abstract : Purpose : To compare the accuracy of total keratometry (TK) and standard keratometry (K) from a swept‐source optical coherence tomography biometer for intraocular lens (IOL) power calculation in eyes with previous corneal refractive surgery. Setting : Cullen Eye Institute, Baylor College of Medicine, Houston, Texas, USA. Design : Retrospective case series. Methods : The differences between the TK and K and their association with K were assessed. For IOL power calculation, combinations of 1) K with Haigis, Haigis‐L, and Barrett True‐K, and 2) TK with Haigis (Haigis‐TK) were used. The mean absolute error (MAE) and the percentages of eyes within prediction errors of ± 0.50 diopters (D), ± 1.00 D, and ± 2.00 D were calculated. Results : The study comprised 129 eyes. For Haigis, Haigis‐L, Barrett True‐K, and Haigis‐TK, respectively, the MAEs were 0.72 D, 0.61 D, 0.54 D, and 0.50 D in the myopic laser in situ keratomileusis (LASIK)/photorefractive keratectomy (PRK) group, and 0.74 D, 0.68 D, 0.71 D, and 0.70 D in hyperopic LASIK/PRK group. For the radial keratotomy (RK) eyes, the MAEs were 0.66 D, 0.71 D, and 0.72 D for the Haigis, Barrett True‐K, and Haigis‐TK formulas, respectively. In the myopic LASIK/PRK group, the Barrett True‐K and Haigis‐TK produced significantly lower MAEs than did Haigis ( P < .05). In the hyperopic LASIK/PRK and RK groups, there were no significant differences between the formulas in MAEs and percentages of eyes within the above prediction errors. Conclusions : The performance of the combination of Haigis and TK in refractive prediction was comparable with Haigis‐L and Barrett True‐K in eyes with previous corneal refractive surgery.